Increased Cellular Senescence and Vascular Rarefaction Exacerbate the Progression of Kidney Fibrosis in Aged Mice Following Transient Ischemic Injury - Clements, Meghan E.; Chaber, Christopher J.; Ledbetter, Steven R.; Zuk, Anna (PLOS ONE, 2013)
Recent findings indicate that elderly patients with acute kidney injury (AKI) have an increased incidence of progression to chronic kidney disease (CKD) due to incomplete recovery from an acute insult. In the current study, a co-morbid model of AKI was developed to better mimic the patient population and to investigate whether age exacerbates the fibrosis and inflammation that develop in the sequelae of progressive kidney disease following acute injury. Young (8–10 weeks) and aged (46–49 weeks) C57BL/6 mice were subjected to 30 min bilateral renal ischemia-reperfusion (I/R) to induce AKI. The aged animals have greater mortality and prolonged elevation of plasma creatinine correlating with less tubular epithelial cell proliferation compared to the young. Six weeks post-reperfusion, interstitial fibrosis is greater in aged kidneys based on picrosirius red staining and immunolocalization of cellular fibronectin, collagen III and collagen IV. Aged kidneys 6 weeks post-reperfusion also express higher levels of p53 and p21 compared to the young, correlating with greater increases in senescence associated (SA) β-galactosidase, a known marker of cellular senescence. A higher influx of F4/80+ macrophages and CD4+ T lymphocytes is measured and is accompanied by increases in mRNA of monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α). Importantly, microvascular density is significantly less, correlating with an increase in nitro-tyrosine, a marker of oxidative stress. Collectively, these data demonstrate that prolonged acute injury in the aged animals results in an accelerated progression of kidney disease in a chronic state.